Analisis kecemasan matematis siswa SMP berdasarkan manifestasi perilaku dalam menyelesaikan masalah geometri lingkaran - Meilany Kusuma Ayu; Amalia Mulya Saputri; Rachmalia Vinda Kusuma (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
Mathematics learning is not only influenced by students' cognitive abilities, but also psychological factors. This study aims to analyze students' mathematical anxiety based on behavioral manifestations. This study uses a qualitative approach with a descriptive type involving 30 students of class VIII at SMPN 5 Tuban. Data were collected through questionnaires, observations, tests, and interviews, then analyzed using the stages of data reduction, data presentation, and drawing conclusions with triangulation. The results showed that in general, students' mathematical anxiety was in the low category (average 57.85%). Based on the aspects of mathematical anxiety, the affective aspect obtained the highest percentage of 62.29% (moderate), while the cognitive aspect of 56.88% and the somatic aspect of 54.38% (low). Observations showed that mathematical anxiety manifested itself through doubts about answers, difficulty determining solution strategies, changes in work steps, and physiological responses such as body tension, trembling hands, sweating, and a pounding heart. Interviews confirmed that mathematical anxiety is not only related to cognitive abilities but is also influenced by affective factors and somatic responses during the process of solving circular geometry problems.